Detrital Thermochronometry Reveals That the Topography Along the Antarctic Peninsula is Not a Pleistocene Landscape. Issue 6 (15th June 2020) - Clinger, Anna E.; Fox, Matthew; Balco, Greg; Cuffey, Kurt; Shuster, David L.
Abstract: Using offshore detrital apatite (U‐Th)/He thermochronometry and 3D thermo‐kinematic modeling of the catchment topography, we constrain the timing of major topographic change at Bourgeois Fjord, Antarctic Peninsula (AP). While many mid‐latitude glacial landscapes developed primarily in response to global cooling over the last ~2.6 Ma, we find that kilometer‐scale landscape evolution at Bourgeois Fjord began ~30–12 Ma ago and <2 km of valley incision has occurred since ~16 Ma. This early onset of major topographic change occurred following the initiation of alpine glaciation at this location and prior to the development of a regional polythermal ice sheet inferred from sedimentary evidence offshore of the AP. We hypothesize that topographic change relates to (i) feedbacks between an evolving topography and glacial erosion processes, (ii) effects of glacial‐interglacial variability, and (iii) the prevalence of subglacial meltwater. The timing and inferred spatial patterns of long‐term exhumation at Bourgeois Fjord are consistent with a hypothesis that glacial erosion processes were suppressed at the AP during global Plio‐Pleistocene cooling, rather than enhanced. Our study examines the long‐term consequences of glacial processes on catchment‐wide erosion as the local climate cooled. Our findings support the hypothesis that landscapes at different latitudes had different responses to global cooling. Our results also suggest that erosion is enhanced along the plateau flanks of Bourgeois Fjord today, which may be due to periglacial processes or mantling via subglacial till. If regional warming persists and meltwater becomes more pronounced, we predict that enhanced erosion along the plateau flank will accelerate topographic change. Key Points: Major topographic change initiated ~30‐12 Ma ago at Bourgeois Fjord, Antarctica Peninsula The timing of topographic change was likely in response to the onset of alpine glaciation and not in response to Plio‐Pleistocene cooling Sediment sourcing scenarios scaled by ice velocity cannot completely describe the detrital distribution of (U‐Th)/He ages